Is Turkish FRAX® Model Sufficient? The Analysis of Osteoporotic Fracture Risk in Turkish Population by Using Frax - Ahmet Aslan; Şule Yağc; Özgür Karakoyun (Galenos Yayinevi, 2014)
Objectives: In this study, we aimed to evaluate the effectiveness of Turkish FRAX model in the prediction of osteoporotic fracture risk and to determine the factors that may affect the results in this model. Material and Methods: Data of 104 patients with hip fracture who had underwent bone densitometry scan between 2009-2012, in Kastamonu and Afyon cities in Turkey, were assessed in this study. Patients were divided into 3 groups. Group-1; patients with osteoporotic hip fractures (n=36), Group-2; patients with other osteoporotic bone fractures (n=33), Group-3; patients with no osteoporotic fracture history (n=35). The recent osteoporotic fractures in patients were ruled out and by noting the former fractures and previously determined risk factors, fracture risks were calculated by Frax method. The groups were compared on the basis of fracture risks, t-scores and demographical characteristics. Results: A statistically significant difference was found between the patients with major osteoporotic fracture (MOF) in Group-1 and Group-2 and patients with no MOF history in Group-3 (p<0.05). When t-scores were compared between the groups, there was difference between Group-1 and Group-3 (p<0.05), there was no difference between Group-2 and 3 (p>0.05). With respect to average age in patients, a significant difference was found between Group-1 and 3(p<0.05), however, no statistical difference between Group-2 and Group-3 (p>0.05). Also, no statistically meaningful difference with regard to other risk factors was found between the groups (p>0.05). Conclusion: Results of this study: previous MOFs, advanced age and a remarkable decrease in t-scores are the main risk factors in osteoporotic fractures. Turkish FRAX® model may be useful in the prediction of fracture risk in patients with increased risk factors in Turkish population. However, this study may not be adequate to rule out the concerns that Turkish Frax model must be revised to fulfill the expectations in determining osteoporotic fracture risk. (Turkish Journal of Osteoporosis 2014;20: 21-5)